Attitudes toward breastfeeding practices among breastfeeding women in Buraydah city, Saudi Arabia: a cross-sectional study - Alharbi, Alhanof F.; Almutairi, Asma M.; Alrasheedi, Abeer E.; Aldukhayel, Abdulrhman; Almutairi, Sara M. (International Journal of Advances in Medicine, 2020)
Background: This study assessed the attitudes toward breastfeeding among mothers receiving healthcare services in Primary Healthcare Centers (PHCCs) in Buraydah, Saudi Arabia. It also examined the association between the mothers’ demographic characteristics and breastfeeding attitudes. Methods: This study utilized a descriptive cross-sectional design. A purposive sample of 415 breastfeeding mothers who were receiving healthcare services from the selected PHCCs during the conduct of the study were recruited in PHCCs in Buraydah, Saudi Arabia. A two-part self-administered questionnaire containing a demographic sheet and the Iowa Infant Feeding Attitude Scale (IIFAS) Arabic version was employed to collect data from the respondents. Descriptive and inferential statistics were used accordingly in data analyses. Results: The overall mean score of the women in the IIFAS was 60.50 (SD = 11.08), with individual scores ranging from 17.00 to 82.00. This finding implies good attitudes toward breastfeeding. Mothers who were divorced/widowed (M = 63.75, SD = 5.20) had significantly better breastfeeding attitudes than married mothers (M = 60.24, SD = 11.38). Mothers who were not working (M = 61.41, SD = 10.03) reported more positive breastfeeding attitudes compared with working mothers (M = 58.36, SD = 13.02). Conclusions: The mothers reported good attitudes toward breastfeeding, but expressed poor beliefs in some areas of breastfeeding. The present findings have implication to medicine, nursing, and healthcare policies.